Diseño de un prototipo de horno para secado de pinturas en la industria de pequeñas producciones utilizando energía renovable. - Encalada Herrera, Cristian David (2013)
This paper aims to design a prototype oven for drying paint, a process that currently is of great importance because of the quality requirements demanded by finished products ranging from the automotive industry to light industry, whether Furniture and household appliances. The prototype is designed furnace through a metal structure which has at its base welded beams to increase resilience to stresses which distort its geometry, and steel plates have inwardly and outwardly to cover the sides of the prototype, it has 2 doors and is protected with a thermal insulator to prevent heat escaping. The oven is heated by electric heaters which are supplied in compliance with global policies of energy conservation, renewable energy.